Genomic Insights into the Role of cAMP in Carotenoid Biosynthesis: Enhancing β-Carotene Production in Escherichia coli via cyaA Deletion - Kwon, Soon Jae; Park, Chan Bae; Lee, Pyung Cheon (International Journal of Molecular Sciences, 2024)
The gamma-ray-induced random mutagenesis of an engineered β-carotene-producing Escherichia coli XL1-Blue resulted in the variant Ajou 45, which exhibits significantly enhanced β-carotene production. The whole-genome sequencing of Ajou 45 identified 55 mutations, notably including a reduction in the copy number of cyaA, encoding adenylate cyclase, a key enzyme regulating intracellular cyclic AMP (cAMP) levels. While the parental XL1-Blue strain harbors two copies of cyaA, Ajou 45 retains only one, potentially leading to reduced intracellular cAMP concentrations. This reduction may alleviate catabolite repression and redirect metabolic flux toward the β-carotene biosynthesis pathway. To validate this mechanistic insight, a targeted cyaA knockout was engineered in XL1-Blue, and its β-carotene production and growth phenotypes were compared with those of Ajou 45 and XL1-Blue. The findings demonstrated that a reduced cyaA copy number substantially enhances β-carotene biosynthesis by modulating cAMP-mediated regulatory networks. This study highlights the efficacy of integrating random mutagenesis with integrative genomic analysis for microbial strain engineering and presents a novel strategy for enhancing carotenoid production in E. coli.
Keywords: Adenylyl Cyclases; beta Carotene; Carotenoids; Cyclic AMP; Escherichia coli; Escherichia coli Proteins; Gene Deletion; Gene Expression Regulation, Bacterial; Genome, Bacterial; Genomics; Metabolic Engineering; Mutagenesis; cAMP; cyaA; mutation; β-carotene